Levels of Anxiety of High School Students when Learning Biology during the Covid-19 Pandemic - Tita Azizah Ghasani; Anda Juanda; Yuyun Maryuningsih (Scientiae Educatia: Jurnal Pendidikan Sains, 2021)
Distance learning is a new learning model for students and teachers. Therefore, it requires a long time to adapt. This study aimed to describe students' attitudes towards anxiety. The research population was SMA NU Juntinyuat, and the research sample was 80 students of class ten. The data were collected using the questionnaires of student anxiety levels and student strategies. This study revealed that 44 students had a very anxious category while 36 students had an anxious type. The high school students' strategy to deal with anxiety showed that 50 students were in the anxiety category while 30 students were in the moderate coping category. These findings concluded that most students had a high anxiety level in learning biology. Meanwhile, students' strategies to solve anxiety were classified as a moderate-coping strategy in anxiety.